Seismic performances of AAC masonry: a review of experimental and numerical approaches: Verhalten von Porenbetonmauerwerk unter seismischen Einwirkungen: eine Überprüfung der experimentellen und numerischen Ansätze. Issue 5 (30th August 2018) - Miccoli, Lorenzo
Abstract: Autoclaved aerated concrete (AAC) has been of growing interest for its structural performances, thanks to its high strength‐to‐weight ratio and low bulk density. The prominent advantage of AAC is its lightweight, this aspect in seismic‐prone areas can be beneficial for the seismic performances of a building. The focus of this paper is to provide an overview of seismic performance of load‐bearing masonry made of AAC, based on the past studies carried out in this field. Results on the assessment of the in‐plane cyclic response of walls with and without reinforcements are reported. In addition, the response of an AAC confined masonry buildings tested on the shaking table is presented. The second part of the paper shows the numerical simulation of the building response based on linear and nonlinear static (push‐over) methods. According to authorś findings, unreinforced AAC masonry buildings with a regular geometry can face low to medium seismic events. For severe seismic events, a significant damage can be expected in AAC multistorey buildings. To achieve higher seismic performance, the AAC masonry must be combined with other structural systems as confined masonry or bed‐joint reinforced walls.